The Effectiveness of the Role of Vessel Traffic Service (VTS) in Monitoring the Order of Ship Movement and the Docking Area in the West Shipping Channel of Surabaya - Rizky Cahyaningrum; Dahri, Muhammad; Purwitasari, Diyah; Johanda Putri, Indah Ayu (Meteor STIP Marunda, 2025)
Vessel Traffic Service (VTS) plays an important role in maintaining the safety and order of ship traffic, especially in congested water areas such as the West Shipping Channel of Surabaya. With this system, it is hoped that the movement of ships can be more organized, so that the risk of accidents and violations can be minimized. However, the effectiveness of VTS in supporting the monitoring of the order of ship movement and berth areas still needs to be further studied. This study aims to analyze the effectiveness of Vessel Traffic Service (VTS) in supporting the monitoring of the order of ship movement and the berth area in the West Shipping Channel of Surabaya. This study uses a quantitative method with a simple linear regression approach. Data was collected through observation and analysis of secondary data, then processed using the SPSS 22 application. The results showed that the effectiveness of VTS had a significant effect on order monitoring, with a significance value of 0.001 less than 0.05. The value of the determination coefficient is 29.1% which means that the effectiveness of VTS contributes to the orderliness of ship movements and the berth area, and from the regression equation obtained it shows that every increase in the effectiveness of VTS by one unit will increase the monitoring of order by 0.470 units.